2017
DOI: 10.1016/j.virol.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

RNA stability regulates human T cell leukemia virus type 1 gene expression in chronically-infected CD4 T cells

Abstract: Regulation of expression of HTLV-1 gene products from integrated proviruses plays an important role in HTLV-1-associated disease pathogenesis. Previous studies have shown that T cell receptor (TCR)- and phorbol ester (PMA) stimulation of chronically infected CD4 T cells increases the expression of integrated HTLV-1 proviruses in latently infected cells, however the mechanism remains unknown. Analysis of HTLV-1 RNA and protein species following PMA treatment of the latently HTLV-1-infected, FS and SP T cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Moreover, p30 II posttranscriptionally inhibits Tax-dependent HTLV-1 gene expression by inhibiting the nuclear export of the pX -encoded tax/rex mRNA (Nicot et al, 2004; Younis et al, 2004; Younis et al, 2006). As Lin et al, 2017 have shown that the stability of tax/rex transcripts modulates HTLV-1 gene expression, it remains unclear whether the p30 II - tax/rex mRNA axis might affect the stability of these transcripts. Lentiviral p30 II interacts with the 20S proteasome activator, REGγ, and reduces the intracellular levels of the pro-apoptotic ataxia telangiectasia mutated (ATM) kinase and increases the survival of transduced Jurkat lymphocytes (Anupam et al, 2011; Doueiri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p30 II posttranscriptionally inhibits Tax-dependent HTLV-1 gene expression by inhibiting the nuclear export of the pX -encoded tax/rex mRNA (Nicot et al, 2004; Younis et al, 2004; Younis et al, 2006). As Lin et al, 2017 have shown that the stability of tax/rex transcripts modulates HTLV-1 gene expression, it remains unclear whether the p30 II - tax/rex mRNA axis might affect the stability of these transcripts. Lentiviral p30 II interacts with the 20S proteasome activator, REGγ, and reduces the intracellular levels of the pro-apoptotic ataxia telangiectasia mutated (ATM) kinase and increases the survival of transduced Jurkat lymphocytes (Anupam et al, 2011; Doueiri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%